2015
DOI: 10.4103/0974-2700.150397
|View full text |Cite
|
Sign up to set email alerts
|

Luxatio erecta humeri: Report of a swimming injury with analysis of the mechanism of the injury and associated injuries in literature

Abstract: Inferior shoulder dislocation also referred to as luxatio erecta is an unusual and rare type of shoulder dislocation. Its incidence is about 0.5% among all shoulder dislocations. After an exhaustive search of all the available literature we were unable to find a swimming accident case that did not have other associated injuries and an uneventful reduction. The mechanism of the injury was mostly related to direct axial loading and indirect hyperabduction lever arm. We would like to emphasize the importance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
(75 reference statements)
0
10
0
1
Order By: Relevance
“…The authors reported that the most frequent mechanism was falling [3]. However, our patient was a construction worker who was rescued from a collapsed building; no other cases have been associated with the same mechanism, in either the review of Gökkuş et al or the other studies.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The authors reported that the most frequent mechanism was falling [3]. However, our patient was a construction worker who was rescued from a collapsed building; no other cases have been associated with the same mechanism, in either the review of Gökkuş et al or the other studies.…”
Section: Discussionmentioning
confidence: 64%
“…This rare dislocation may occur from a direct or indirect mechanism, the majority of which result from falling accidents [2, 3]. The first and most common mechanism is a direct loading force on a fully abducted arm, as seen on our case.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…La luxación de hombro en niños es una entidad infrecuente, siendo sumamente rara la luxación erecta o glenohumeral inferior, se desconocen cifras certeras de su incidencia (1)(8) (10) .…”
Section: Introductionunclassified
“…on their insightful and unique description of luxatio erecta humeri as a result of a swimming injury. [ 1 ] This is a quite rare but fascinating pathologic condition which can present physicians with a significant treatment challenge. I applaud the authors for publishing their report in a journal with open access so that all physicians who may encounter this injury can easily access the information required to effectively render treatment for these patients.…”
mentioning
confidence: 99%